157 EXPRESSION OF THE MER PROTO-ONCOGENE IN T CELL ACUTE LYMPHOBLASTIC LEUKEMIA PATIENTS IS ASSOCIATED WITH AN EARLY T CELL STAGE OF DIFFERENTIATION. (1st January 2005) - Cao, J.; Salzburg, D. B.; Sather, S.; Keating, A. K.; Graham, D. K.
Abstract : Tyrosine kinases play an important role in normal cellular growth and differentiation. Abnormal tyrosine kinase activity can result in cellular transformation leading to the development of human cancer. The Mer receptor tyrosine kinase, initially cloned from a human B lymphoblastoid cell line, is expressed in a spectrum of hematopoeitc, epithelial, and mesenchymal cell lines. Interestingly, while the Mer RNA transcript is detected in numerous T and B lymphoblastic cell lines and acute lymphoblastic leukemia (ALL) patient samples, Mer RNA is not found in normal human thymocytes, lymphocytes or in PMA/PHA stimulated lymphocytes. To further investigate the role of human Mer in leukemogenesis, a monoclonal antibody was developed that specifically recognizes human Mer. Using this antibody, we have screened 16 T-cell ALL patient samples by Western Blot. Among these 16 patients, 9 of the patients demonstrated ectopic expression of hMer. None of the ALL patient samples evaluated expressed the Axl protein, a member of the Mer tyrosine kinase subfamily. We analyzed lymphoblasts from 16 T cell ALL patients diagnosed between July 1995 and July 2004 at The Children's Hospital, Denver for Mer protein surface expression. Of the T cell ALL patient samples, we found that 9/16 (56%) were positive for Mer protein surface expression. A novel, smaller form of Mer was detected in one patient sample which may represent a truncated Mer protein. Sequence analysis of the Mer gene in the patient samples is underway to evaluate for mutations that may lead to constitutive Mer tyrosine kinase activity. Although we were not able to statistically evaluate the clinical outcomes relative to Mer expression due to the study sample number, there was a statistically significant association between positive expression of Mer and lack of surface expression of CD3 (p = 0.04). We found that 7/9 (78%) of Mer positive lacked CD3 surface expression, while only 1/6 (17%) of the Mer negative patients lacked CD3 surface expression. Lymphoblasts that lack surface expression of CD3 represent an immature phenotype and have been associated with a decreased event free survival as compared with surface positive CD3 lymphoblasts. Further investigation of the ectopic expression of Mer in lymphoblasts may reveal the use of this novel Mer glycosylated protein as a prognostic marker and possibly a future therapeutic target in the treatment of childhood leukemia.